Utilization of Organic Banana Peel Waste as an Alternative Material for Making Environmentally Friendly Ice Cream - Imelda, Dewi Qomariah; Hariyati, Tati; Ningsih, Resky Ayu; Nugroho, Prisma; Respita, Reny; Sari, Dwi Alya Amanda (Edumedia Solution, 2025)
Banana peels are an abundant organic household waste that has not been optimally utilized. This community service activity aims to empower community groups through training in making banana peel-based ice cream as a functional food product that is environmentally friendly and has economic value. The implementation method includes socialization, technical training in processing banana peels into flour, ice cream formulation, packaging, and mentoring for household-scale businesses. The activity was carried out in Tanjung Selor, Bulungan Regency, targeting students of the University Kaltara. The results of the implementation showed an increase in participants' skills in processing waste into products with sales value, as well as the emergence of interest in developing local food-based businesses. This program also supports the implementation of a circular economy and the reduction of organic waste through an innovative community-based approach.